KAJIAN YURIDIS TERHADAP AKTA PELEPASAN HAK DENGAN GANTI RUGI YANG LAHIR AKIBAT WANPRESTASI HUTANG PIUTANG - ELLYS NOVITA BANJARNAHOR (PREMISE LAW JURNAL, 2016)
Credit contract occurs when someone needs fund and it is provided by a creditor in a form of a contract. It is closely related to collateral since every credit needs security on the fund which is borrowed. The insurance of the reimbursement is indicated by collateral in mortgaging a debtor’s property for the reimbursement. If the debtor cannot pay off this debt, the collateral cannot be directly transferred to the creditor. The research used descriptive analytic and judicial normative method. The conclution of the study was that the legality of the result of PHGR is legally null and void. Its legal consequence is because its settlement is not certain since the MPD (Regional Supervisory Council) of Medan did not get any report from the parties concerned of this case. It is recommended that Notaries have prudential principles, more prudent, moral and ethics. The MPD of Medan should be more careful in examining and controlling which are reported by Notaries each month. Keywords: Renunciation of Rights and Titles and Indemnity Certificate, Default, Credit Contract